NEW CREATIVITY EMERGING OUT OF DESTRUCTION: THE DADA MOVEMENT - UZ, Ayfer (Atlas Journal, 2020)
The Dada movement, also known as Dadaism, began at about the same time in the cities of Zürich and New York in 1916 during the First World War. It soon spread to Europe's other cultural centers, North and South America, and then it disappeared in 1923. Dada was a struggle to save the art from the monopoly of certain segments of society and to question the supreme value attributed to art. It purported to reach its goals through acts of destruction, ridicule and taking in the form of alienation leading to a kind of demolition. The purpose of all the destructive actions of Dada to attack sturdy values, fake authorities, and ridiculing the stinking institutions was to open the eyes of the people and to make them conscious of their condition. This counter-stance cried out in a multi-faceted manner, which was a social, political, economic indicator of a significant approach. Consequently, it has become the most important art movement of the 20th century that wanted to break down multiple objects, to look back on its importance in new artistic creativity which has come together with destruction. In this study, research data were analyzed by the "descriptive analysis" method.